Prevention of hepatocellular carcinoma in the Asia-Pacific region: Consensus statements - Farrell, G.C.; Chan, H.L.Y.; Yuen, M.F.; Amarapurkar, D.N.; Chutaputti, A.; Fan, J.G.; Hou, J.L.; Han, K.H.; Kao, J.H.; Lim, S.G.; Mohamed, R.; Sollano, J.; et al. (Blackwell Publishing, 2010)
Among approximately 650 000 people who die from hepatocellular carcinoma (HCC) each year, at least two-thirds live in Asia. Efforts to improve early diagnosis and treatment have not yet impacted mortality. An Asia-Pacific Working Party convened in Hong Kong in June 2008 to consider ways to prevent HCC in this region. Separate reviews have summarized epidemiology of HCC, preventive approaches related to hepatitis B virus (HBV), hepatitis C virus (HCV) and non-viral liver diseases, and the role of surveillance to detect HCC at a curative stage. We now present Consensus Statements from these deliberations and reviews. As chronic hepatitis B is the most common cause of HCC in Asia, effective hepatitis B vaccination programs are the most important strategy to reduce HCC incidence. Prevention of HCV by screening blood donors, universal precautions against blood contamination in health-care settings and reducing HCV transmission from injection drug use are also vital. There is strong evidence that effective antiviral therapy to control HBV infection or eradicate HCV substantially reduces (but does not abolish) HCC risk. With hemochromatosis, family screening, early diagnosis and correcting iron overload to prevent liver fibrosis prevents HCC. There is currently insufficient evidence to give firm recommendations on alcohol, obesity/metabolic risk factors and other liver diseases. HCC surveillance for high-risk groups is recommended in individual cases but cost-effectiveness is not as high as infant hepatitis B vaccination and screening blood for HCV. Widespread application of HCC surveillance in Asia-Pacific countries depends on economic factors and health-care priorities.